Spatio-Temporal Variability Analysis of Rainfall in Kumadugu-Yobe River Basin, Nigeria - Ahmed Abubakar Jajere; Ajiya Bulus Sawa; Usman Ado Kibon; Bibi Umar Muhammed; Modibbo Babagana-Kyari (Geosfera Indonesia, 2022)
Large-scale climatic variability is seriously affecting rainfall and temperature distribution pattern in Sudano-Sahelian parts of Lake Chad Basin. The Kumadugu-gana and Yobe Rivers that drain the south-western part of the Lake Chad Basin now flow for six months only in a year instead of nine, and this has affected the entire ecosystem of the basin. This study examines the spatio-temporal variability of Kumagu-Yobe river basin rainfall. The study used monthly rainfall records for 1981-2017 from five different weather stations that spread across the up-and-downstream parts of the basin. To accomplish the objective of the study descriptive and inferential statistics were used in analyzing the rainfall attributes and temporal distribution pattern for each of the stations during the study period. Linear regression model was used in analyzing the stations rainfall temporal variability trend. The findings of the study revealed a large scale spatio-temporal variability in the distribution of the rainfall attributes during the study period. Generally, the basin recorded increasing trend of rainfall within the study period. Annual increasing trends of 1.1mm, 3.1mm, 17.6mm and 17.2mm were observed at Potiskum, Nguru, Bauchi and Kano stations respectively. Thus, Jos records insignificant decreasing trend of -0.2mm annually. Specifically, a variability of less than 1% was also observed at Jos and Potiskum stations which is statistically insignificant. A variability of 19%, 28% and 44% was observed at Nguru, Kano, Jos, and Bauchi respectively. Overall, throughout the study periods the basin recorded increasing trend of rainfall that is characterised with large scale fluctuations particularly at the upstream section of the basin. However, desertification and upstream water abstraction may have reduced any noticeable increase in stream downstream Keywords : River Yobe, Kumadugu-Yobe Basin, Rainfall, Spatio-Temporal variability Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License